2007
DOI: 10.1016/j.jtcvs.2006.10.066
|View full text |Cite
|
Sign up to set email alerts
|

The adverse effect of back-bleeding from lumbar arteries on spinal cord pathophysiology in a rabbit model

Abstract: Rabbits with 15-minute aortic clamping in the infrarenal portion showed delayed paraplegia, and those with back-bleeding from lumbar arteries showed early onset of paraplegia. The prevention of back-bleeding from intercostal arteries and lumbar arteries during thoracoabdominal aortic surgery was considered to reduce spinal ischemic injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…[41][42][43] The only case of spinal cord ischemia we reported in our series was a delayed transient paraplegia that occurred in 1 patient in the hybrid group in which an intercostal artery patch with a patent intercostal artery was unintentionally partially covered. The delayed symptoms completely resolved with emergent spinal fluid drainage.…”
Section: Discussionmentioning
confidence: 84%
“…[41][42][43] The only case of spinal cord ischemia we reported in our series was a delayed transient paraplegia that occurred in 1 patient in the hybrid group in which an intercostal artery patch with a patent intercostal artery was unintentionally partially covered. The delayed symptoms completely resolved with emergent spinal fluid drainage.…”
Section: Discussionmentioning
confidence: 84%
“…MEPs are used perioperatively to monitor spinal cord ischemia continuously. Some intercostal arteries responsible for the spinal cord ischemia are aggressively reattached according to the preoperative demonstration of the AKA by MRI or CT scans [67], while controlling back-bleeding from the other intercostal arteries without delay [68,69]. On the other hand, Kouchoukos et al employed systemic deep hypothermia for protection of the spinal cord as well as the brain in dTAA and TAAA repair in 1995 [70].…”
Section: Spinal Cord Protection During Aortic Surgerymentioning
confidence: 99%
“…In a porcine experimental study, we found that controlling the back-fl ow from the intercostal arteries in the opened aorta maintained higher blood fl ow of the cord during aortic clamping and resulted in a better neurological outcome compared with the controls. 42 Griepp et al underscored the importance of clamping the intercostal arteries externally prior to opening the aorta to prevent cord ischemia. 43…”
Section: Effect Of Aortic Cross-clampingmentioning
confidence: 99%
“…53 We have experimentally demonstrated that controlling the intercostal back-fl ow in the porcine opened aorta could reduce the incidence of spinal cord ischemia. 42 Thus, external clamping of the intercostal arteries before opening the aneurysm or intraluminal insertion of a 2F balloon-tipped catheter into the intercostal arteries after opening the aneurysm is routine for minimizing blood refl ux from the intercostal arteries.…”
Section: Efforts To Minimize Blood Steal From the Spinal Cordmentioning
confidence: 99%